Comparison of Germ Count Levels Based on Zone at Central Operating Theatre Facility Dr. Soetomo General and Academic Hospital - Ismawati, Nining Dwi Suti; Kurniati, Neneng Dewi; Nugraha, Andreas Pratama; Baehaqi, Ronny; Taufiqurrahman, Irham; Nurrahman, Tri (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2025)
Central of Disease Control state that Healthcare-Assoxiated Infections (HAI’s) prevalence on Surgical Site Infection (SSI) reach up 121.800 in patient surgery cases and increase mortality risk up to 12-times. Surgical site infection (SSI) are one of the causes of morbidity, mortality, increased length of stay, costs, and patient complaints, including in orbital surgery. This study was conducted at Central Operating Theatre Facility Dr. Soetomo General and Academic Hospital as surgical service facility includes 22 operating room and supporting facilities. Therefore, the Central Operating Theater Facility is higher risk of nosocomial infection. The purpose of this study was to compare the floor germs and air germs based on zones in the Central Operating Theater Facility. This study was done from September 2023 to December 2024 with cross-sectional quantitative and observational method. Total population are 43 rooms with sample size of  26 rooms were calculated using Lemeshow formula and the locations are determined randomly. Data analysis used Kruskal-Wallis test to compare the variable and descriptive analysis used frequency distribution. The results show significant difference in the counts of germ floor based on zones (p-value 0.047) and there is significant difference in the counts of germ air based on zones (p-value 0.047) at Central Operating Theater Facility. The most common germ found on floors is Staphylococcus haemolyticus, while the most common germ found in the air is Staphylococcus epidermidis.